2001
DOI: 10.1210/endo.142.7.8264
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Undernutrition during Early to Midgestation Programs Tissue-Specific Alterations in the Expression of the Glucocorticoid Receptor, 11β-Hydroxysteroid Dehydrogenase Isoforms, and Type 1 Angiotensin II Receptor in Neonatal Sheep*

Abstract: We have investigated the effects of maternal nutrient restriction in the sheep during the period of rapid placental growth (i.e. 28-77 days gestation; term = 147 days) on feto-placental growth and expression of the glucocorticoid receptor (GR), types 1 and 2 11beta-hydroxysteroid dehydrogenase (11betaHSD1, 11betaHSD2), and types 1 and 2 angiotensin II receptor (AT1, AT2) in fetal and neonatal offspring. Ewes (n = 63) of similar age, body weight, and body composition were randomly allocated to a nutrient-restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(45 citation statements)
references
References 43 publications
2
43
0
Order By: Relevance
“…Previous work found that maternal protein restriction leads to down-regulation of 11b-hydroxysteroid dehydrogenase-2 in placenta and consequently, increased foetal exposure to maternal glucocorticoids [19,20,25,26]. This has been proposed to underlie the effects of low-protein diet on offspring phenotypes such as development of hypertension [20,23].…”
Section: Discussionmentioning
confidence: 98%
“…Previous work found that maternal protein restriction leads to down-regulation of 11b-hydroxysteroid dehydrogenase-2 in placenta and consequently, increased foetal exposure to maternal glucocorticoids [19,20,25,26]. This has been proposed to underlie the effects of low-protein diet on offspring phenotypes such as development of hypertension [20,23].…”
Section: Discussionmentioning
confidence: 98%
“…These findings indicate the sensitivity of both UCP1 and 2 to glucocorticoid status around the time of birth. 12,35 The extent to which a change in local cortisol synthesis via the enzyme 11βHSD1, which is predicted to be enhanced, 36 rather than direct stimulation of the GR receptor that is one potential stimulus for the rise in UCP remains to be clarified. With regard to the more immediate effects of maternal dexamethasone administration on fetal adipose tissue maturation, it was only gene expression for UCP2 that was raised prior to the onset of breathing.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in utero exposure to dexamethasone causes a marked increase in GR expression and attenuated fatty acid uptake in adult rats, selectively in visceral adipose tissue, which may contribute to both adipose and hepatic insulin resistance [81]. Maternal nutrient restriction during pregnancy has also been associated with increased adipose tissue GR expression and obesity in sheep [90][91][92].…”
Section: Programming Of Muscle and Fatmentioning
confidence: 99%